The influence of design and typography on packaging effectiveness in the perception of the customers (radix fried chicken) / Mohd Ikhmal Fadzil - Fadzil, Mohd Ikhmal (Faculty of Business Management, 2010)
The effectiveness of food packaging design and the role of product packaging as a vehicle for consumers’ perception is an issue that is globally discussed. The purpose of this study is to examine the effectiveness of Radix Fried Chicken food product packaging in relation to Malaysian customers’ perception. Effectiveness of packaging is very important for RFC as this phenomenon was found in the previous study to contribute to the increase of sales return. This study is currently important because effective food packaging is one of the problems that arise among RFC especially in enhancing high sales and pin filtration strategy in the global market. To achieve effectiveness of food product packaging goals, knowledge about consumer psychology is important. RFC need to understand consumer response to their packages in order to increase their sales. This paper also seeks to discuss the need to understand consumers’ perception in order to correctly design the packaging with suitable colour, typography and convenient of usage to the customers. Two independent variables were chosen related to design and graphical form and typography. This study will report on the findings of 160 Northern Malaysian RFC customers randomly chosen to response on the questionnaires at the 3 RFC restaurants in the Northern area. The evaluation of Northern Malaysian customers’ perception holds importance to RFC who need to understand the right food packaging in the eyes of their customers.